Essential normality of some classes of operators in infinite tensor products of Hilbert spaces - Livinskii, V. O. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
The essential normality of some classes of operators in stabilized infinite tensor products of Hilbert spaces is established by using the general criteria for the domains of definition of spectral integrals to be essential.